Analyzing indications for caesarean delivery in a tertiary care facility in India by Robsons Ten Group Classification System: journey to reduce maternal mortality-audit caesarean rates: a prospective observational design - Mahadik, Kalpana; J. S., Shany John; Vohra, Shivangani (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: Rising caesarean rates pose a challenge to obstetricians, the healthcare system, and the national economy. High rate of caesarean without clear evidence of a decrease in maternal and neonatal morbidity is matter of concern. The era of impatient obstetricians, and caesareans on demand are major contributing factors. The purpose of this study is to validateTGCS classification for indications of caesarean. This would help to audit and streamline the indications of caesarean. Standardization of indications is the need of the hour. Learning from what has happened in background of local situations is the main aim of this work. Methods: In a prospective observational design, 1140 women who underwent caesarean for varied indications in C R Gardi Hospital Ujjain were recruited. Patients were classified according to Robson’s Ten Group Classification System. Every woman was observed for post-cesarean morbidities like wound dehiscence, anemia, postpartum hemorrhage, and puerperal sepsis. Neonates were observed for NICU admission, low birth weight, prematurity, respiratory distress syndrome, meconium aspiration syndrome, and death. Chi- Square and student t test were used for analysis. Results: 45.8% of women were of group 5. Modifiable indications were 60.2% in the primary caesarean of group 5. PPH, puerperal sepsis, PNC anemia, wound dehiscence, DVT, rupture uterus and NICU admission, respiratory distress syndrome of neonates were significantly high in group 5 ( p= less than 0.05). Conclusions: Out of all caesarean 45.8% are second caesarean for previous one caesarean. PPH, puerperal sepsis, wound dehiscence and PNC anemia are significantly high in group 5.